Calculated estimation of railway wheels equivalent conicity influence on critical speed of railway passenger car - Gerlici Juraj (MATEC Web of Conferences, 2018)
The article presents the results of determining the equivalent conicity characterizing the geometric interaction of wheels and rails on 1520 mm track. The cases of interactions of rails and wheelsets, wheels of which have different profiles, are considered. The computer model of the motion speed of the passenger car is developed. According to the results of computer simulation, critical speeds for the bogie moving through the tracks of indented gauge are received. Based on the results of the simulation analysis, the significant dependence of the value of the equivalent conicity on the critical speed is confirmed. The necessity of considering the limit values of equivalent conicity in tests of high-speed rolling stock is emphasized.